Horizonte Geschichte - Arnold, Daniela; Bode, Matthias 1971-; Baumgärtner, Ulrich 1957-; Fieberg, Klaus 1952-; Peters, Jelko 1969-; Schweppenstette, Frank 1969- (Westermann, 2022)
Französische Revolution bis Erster Weltkrieg
Keywords: Schulbuch